2002
DOI: 10.1021/jp020617y
|View full text |Cite
|
Sign up to set email alerts
|

Formic Acid Adsorption on Anatase TiO2(001)−(1 × 4) Thin Films Studied by NC-AFM and STM

Abstract: Atomic resolution scanning tunneling microscopy (STM), noncontact atomic force microscopy (NC-AFM), X-ray photoemission spectroscopy (XPS), low-energy electron diffraction (LEED), and formic acid adsorption experiments were used to characterize the (001) surface of anatase TiO2. A combination of NC-AFM and STM imaging was used to distinguish features due to geometrical and electronic effects. The contrast in images of the bare (1 × 4) surface and the formate-covered surface is dominated by the surface topograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
110
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(132 citation statements)
references
References 59 publications
(95 reference statements)
20
110
1
Order By: Relevance
“…The effect of steric hindrance by TiO 2 and adsorbed molecules is therefore, explicitly ruled out. According to the literature [62][63][64], the anatase {0 0 1} surface has a strong ability to adsorb hydroxyl and carboxylic groups (as well as water molecules) dissociatively onto the undercoordinated Ti cations. It can therefore, be reasonably concluded that S M basal /S M lateral with synergetic nanocrystal engineering plays an essential role in determining the dye adsorption capability, because the surface areas of the TMC samples are very similar.…”
Section: Dye-sensitized H 2 Evolution Under Visible-light Irradiationmentioning
confidence: 99%
“…The effect of steric hindrance by TiO 2 and adsorbed molecules is therefore, explicitly ruled out. According to the literature [62][63][64], the anatase {0 0 1} surface has a strong ability to adsorb hydroxyl and carboxylic groups (as well as water molecules) dissociatively onto the undercoordinated Ti cations. It can therefore, be reasonably concluded that S M basal /S M lateral with synergetic nanocrystal engineering plays an essential role in determining the dye adsorption capability, because the surface areas of the TMC samples are very similar.…”
Section: Dye-sensitized H 2 Evolution Under Visible-light Irradiationmentioning
confidence: 99%
“…6 Formate adsorption on TiO 2 has been studied extensively. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Previous studies of adsorption of formic acid (HCOOH) on rutile TiO 2 (110) surfaces have shown that upon adsorption it dissociates into a formate ion (HCOO -) and a proton (H + ), which bind to lowcoordinated Ti and O surface atoms, respectively. 22,23 The adsorption structure of small molecules, such as HCOOH, can be studied favourably by infrared spectroscopy, and in particular infrared reflection-absorption spectroscopy (IRRAS) has been employed to study e.g.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray photoelectron diffraction data were consistent with an epitaxial vanadia layer; however, no ordered LEED patterns were obtained. The lack of any discernible order in LEED may have been due to the condition of the anatase (0 0 1) substrate surface which displayed only a (1 · 1) pattern rather than the (4 · 1) reconstruction now considered to be the favored termination for stoichiometric anatase (0 0 1) [15,16]. Thus the structure of vanadia layers on TiO 2 remains an open question.…”
Section: Introductionmentioning
confidence: 99%